Developing the Prototype of Picture-Based Learning Materials in the Teaching of Speaking Skills - Paris Jiwa Karya; Kenza Takarroucht; Kufakunesu Zano; Alex Zamorano (Journal of Language and Literature Studies, 2022)
Various pictures can be utilized as learning media to facilitate language learners to learn vocabulary, pronunciation, grammar, and speaking skills. In the teaching of speaking, serial pictures can be designed to promote students to speak what the pictures illustrate. Therefore, speaking skills become crucial part in learning the target language. In  learning English where learners have limited sources to access real English communication with native or non-native English speakers, speaking materials become essential roles in developing learners’ speaking skills. Unfortunately, most of English Foreign Learners (EFL) oftenly confused to practice their English speaking skill because of  the the laerners are afraid to start the conversation or express their idea in English. Dealing with this issue, this study is aimed at developing the prototype of learning materials in the teaching of speaking skills in high school level. This study is categorized as R&D design (Research & Development). The data consisted of two kinds, quantitative and qualitative data. The quantitative data are collected using questionnaire and speaking tests. Meanwhile, qualitative data are gained using interview sheets. Then, the quantitative data were analyzed using statistical analysis, while the qualitative data were elaborated in qualitative ways. The process of the qualitative ways consisted of three main analyses, namely condensation data, data display, and conclusion drawing/verification. Based on the result of analysis, this study showed that most of the laerners are afraid to making mistakes in speaking English. It was affected by some difficulties like their pronunciation, vocabulary mastery also grammar. For further studies, speaking practices are needed more in learning English speaking to train them to use the language to communicate. The implication for further learning is that speaking materials are designed in line with students’ speaking level and students’ target needs and learning needs.